Warisan Budaya Aceh: Tradisi, Seni, dan Identitas Lokal - Ratna Dewi; Dinda Amara Putri; Fauziyah Fauziyah; Siti Nurelisah; Vira Dwi Amaliah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Aceh is known as a province with cultural diversity and customs that are the outlook on life of its people. Customs are highly preserved because they are ancestral heritage that must be passed on to the next generation. One important aspect of culture is the regional language, which is an inseparable part of people's lives. Language functions as a means of communication to interact and build social relationships. Language is a meaningful expression used to convey messages that can be understood by the listener (Rizky, 2012). The Acehnese people are known to have a strong culture, reflected in the expression "matee aneuk meupat jeurat, gadoh adat pat tamita" which contains deep philosophical values. This expression shows people's awareness of the importance of customs in everyday life. Acehnese customs are an integral part of the culture that continues to live and develop in society. This custom makes a major contribution to the continuity of socio-cultural life in Aceh